Phase instabilities in austenitic steels during particle bombardment at high and low dose rates. (May 2022) - Levine, S.M.; Pareige, C.; Jiao, Z.; Edmondson, P.D.; Was, G.S.; Zinkle, S.J.; Bhattacharya, A.
Graphical abstract: Highlights: Ballistic dissolution of different nanocluster species similarly irradiated can vary. Neutron irradiation forms Cu-rich clusters in 304L but ion irradiation dissolves them. Neutron irradiation-induced Ni-Si-Mn-rich clusters are stable/grow by ion irradiation. A modified Heinig model validated the critical conditions for nanocluster stability. RED and near-interface solute gradients control recovery from ballistic dissolution. Abstract: Disruption of phase stability by energetic particle bombardment is a major challenge in designing advanced radiation-tolerant alloys and ion beam processing of nanocomposites. Particularly, ballistic dissolution susceptibility of different solute nanocluster species in alloys is poorly understood. Here, low dose rate neutron irradiations were conducted on a Fe-Cr-Ni based austenitic steel in the BOR-60 reactor (9.4 × 10 −7  dpa/s, 318 °C) followed by accelerated dose rate ion irradiations at multiple temperatures ( ~ 10 −3 dpa/s, 380 – 420 °C). Using atom probe tomography, the stability of radiation-enhanced Cu-rich and radiation-induced Ni-Si-Mn-rich nanoclusters was evaluated. During neutron irradiation, Cu-rich clusters nucleated with their core concentrations progressively increasing with dose, while Ni-Si-Mn-rich clusters formed and evolved into G-phase precipitates. Ion irradiations dramatically altered the nanoclusters. Cu-rich clusters were ballistically dissolved, but Ni-Si-Mn-rich clusters remained stable and coarsened with dose at 400 and 420 °C, highlighting that different nanocluster species in a single microstructure can have innately distinct ballistic dissolution susceptibilities. Solute-specific recoil rates were incorporated into the Heinig precipitate stability model, which shows that in addition to radiation-enhanced diffusion, recovery from ballistic dissolution depends on solute concentration gradient near cluster interfaces. The combined experimental-modeling study quantified the critical temperatures and damage rates where ballistic dissolution dominates for each cluster species.